IDENTIFICATION OF THE UPSTREAM REGION THAT GIVES SIGNIFICANT IMPACT FOR INCREASE DISCHARGE IN MAJALAYA - Adnan Al Husainy, Muhammad
Majalaya is one of area in Bandung that has many frequent flood events. There are 147 total event of flood in 5 years (2009-2013). There are four upstreams that lead to the Majalaya, namely Kertasari, Pacet, Ibun and Drawati. In March 2016 there were three extreme flood events with different rain location. Therefore, information regarding the upstream region which give significant impact on discharge in Majalaya important to note, especially to reduce the risk of flood. There are 31 scenarios to be simulated in a hydrological model Gridded Surface/Subsurface Hydrologic Analysis (GSSHA) to obtain peak discharge from each scenario. Each peak discharge will be compare to peak discharge from rainy uniform across the region. Then, discharge peak ratio is used to determine the area that give the significant impact for flood in Majalaya. The results showed that the rainfall that occurred in Drawati, Ibun, Pacet and Kertasari simulataneously will produce the highest ratio of discharge, the region most affect the increased discharge in Majalaya is Kertasari and Ibun is the region that has highest flow rate.